Steroid hormone control of cell death and cell survival: molecular insights using RNAi. - Suganthi Chittaranjan; Melissa McConechy; Ying-Chen Claire Hou; J Douglas Freeman; Lindsay Devorkin; Sharon M Gorski (PLoS Genetics)
The insect steroid hormone ecdysone triggers programmed cell death of obsolete larval tissues during metamorphosis and provides a model system for understanding steroid hormone control of cell death and cell survival. Previous genome-wide expression studies of Drosophila larval salivary glands resulted in the identification of many genes associated with ecdysone-induced cell death and cell survival, but functional verification was lacking. In this study, we test functionally 460 of these genes using RNA interference in ecdysone-treated Drosophila l(2)mbn cells. Cell viability, cell morphology, cell proliferation, and apoptosis assays confirmed the effects of known genes and additionally resulted in the identification of six new pro-death related genes, including sorting nexin-like gene SH3PX1 and Sox box protein Sox14, and 18 new pro-survival genes. Identified genes were further characterized to determine their ecdysone dependency and potential function in cell death regulation. We found that the pro-survival function of five genes (Ras85D, Cp1, CG13784, CG32016, and CG33087), was dependent on ecdysone signaling. The TUNEL assay revealed an additional two genes (Kap-alpha3 and Smr) with an ecdysone-dependent cell survival function that was associated with reduced cell death. In vitro, Sox14 RNAi reduced the percentage of TUNEL-positive l(2)mbn cells (p<0.05) following ecdysone treatment, and Sox14 overexpression was sufficient to induce apoptosis. In vivo analyses of Sox14-RNAi animals revealed multiple phenotypes characteristic of aberrant or reduced ecdysone signaling, including defects in larval midgut and salivary gland destruction. These studies identify Sox14 as a positive regulator of ecdysone-mediated cell death and provide new insights into the molecular mechanisms underlying the ecdysone signaling network governing cell death and cell survival.